2006
DOI: 10.1016/j.jms.2006.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of the high sensitivity Fourier transform and ICLAS-VeCSEL absorption spectra of D2O between 8800 and 9520cm−1

Abstract: The absorption spectrum of dideuterated water, D 2 O, has been recorded between 8800 and 9520 cm À1 by intracavity laser absorption spectroscopy (ICLAS) based on a vertical external cavity system emitting laser (VeCSEL) and by high sensitivity Fourier Transform spectroscopy. The combined analysis of the spectra has allowed attributing 1223 transitions to the D 2 O species. The spectrum assignment was performed on the basis of the recent results of variational calculations based on an optimized potential energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Table 2 Rovibrational term values (cm À1 ) of the (3 1 1), (1 1 3), (2 1 2) and (4 1 0 first stage of this study, as well as new data from Refs. [3,16,17] were combined and used by Shirin et al [18] for a further optimization of the D 2 O PES. A new synthetic spectrum [18], referred below as ''calculation 2'', was generated with the new D 2 O PES and again with the DMS of Ref.…”
Section: Spectrum Assignment and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 Rovibrational term values (cm À1 ) of the (3 1 1), (1 1 3), (2 1 2) and (4 1 0 first stage of this study, as well as new data from Refs. [3,16,17] were combined and used by Shirin et al [18] for a further optimization of the D 2 O PES. A new synthetic spectrum [18], referred below as ''calculation 2'', was generated with the new D 2 O PES and again with the DMS of Ref.…”
Section: Spectrum Assignment and Resultsmentioning
confidence: 99%
“…1): the 3m 1 + m 2 + m 3 and the m 1 + m 2 + 3m 3 centered at 11 500.247 and 11 816.636 cm À1 , respectively, belonging to the (m 1 + m 2 / 2 + m 3 ) = 4.5 polyad which is the first pentadecad of resonating states. We have recently reported the analysis of the second decad lying in the 8800-9520 cm À1 from a combined study by FTS with a 600 m path length in Reims and by ICLAS based on vertical external cavity surface emitting lasers (VeCSEL) in Grenoble [3]. This work showed that, in this spectral range, the two experimental approaches have specific advantages but a roughly equivalent sensitivity.…”
Section: Introductionmentioning
confidence: 98%
“…Rovibrational analysis has been used to assign the detected lines [247]. Some of the measured molecular species are nitrous oxide (N 2 O) [245], water (H 2 O) [148,244,[246][247][248], carbon dioxide (CO 2 ) [148,246], hydrogen sulfide (H 2 S) [249], acetylene (HCCH) [248], and carbonyl sulfide (OCS) [250], as well as a variety of isotopic variants such as D 2 O [251]. Prior to the development of semiconductor VECSELs, ICLAS relied primarily on Ti:sapphire laser in the 700-900 nm range and dye lasers in the visible range.…”
Section: à1/2mentioning
confidence: 99%
“…Although several recent papers [1][2][3][4][5][6] have extended to higher energies the experimental investigations of the D 2 O absorption spectroscopy, the highest transitions reported so far have been observed by ICLAS around 12 800 cm À1 [3,6] (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%